Historical Review Of Agrarian Reform Is The Idea Of A Complete Systematic Land Registration Program (Ptsl) That Affects The Land Rights Of The Indonesian People - Rahadian, Rian; Sudjadi, Agung (Ipso Jure, 2024)
Objective – Find out how the PTSL program that Prabowo Subianto will continue is related to the historical journey of agrarian reform in Indonesia. Research method – Using qualitative research methods by analyzing the History Book of the Journey of Agrarian Law in Indonesia or using historical analysis Findings – That the Complete Systematic Land Registration Program (PTSL) originated from Soekarno's Land Reform Ideas. Original - This research analyzes inductively that PTSL is a program that was born because of the thoughts of Indonesia's first president, namely Soekarno.